PSYCHIATRIC EFFECTS OF ANABOLIC-ANDROGENIC STEROIDS (AAS) ON ATHLETES - A COMPREHENSIVE LITERATURE REVIEW - Carmena Luty; Maja Osuch; Maciej Osuch; Olga Tatarata; Martyna Jaciubek; Amanda Abramowicz; Magdalena Rumin; Anna Kiełboń; Zuzanna Olga Reklewska; Kornelia Domagała (International Journal of Innovative Technologies in Social Science, 2026)
Background and Objectives: Anabolic-androgenic steroids (AAS) are synthetic derivatives of testosterone widely misused by athletes to enhance physical performance and appearance. Emerging evidence indicates substantial psychiatric morbidity associated with AAS use. This comprehensive literature review synthesizes empirical evidence from peer-reviewed research published between 2015 and 2025 examining psychiatric effects of AAS among athletic populations. Methods: A systematic search of electronic databases (PubMed, Scopus, Web of Science, Google Scholar) was conducted using keywords related to AAS, psychiatric effects, mental health, and athletes. Studies published in English or Polish between January 2015 and December 2025 were included. Data extraction focused on prevalence, clinical manifestations, neurobiological mechanisms, and treatment implications. Results: Recent epidemiological data indicate AAS prevalence of approximately 10–20% among elite athletes and over 25% among weightlifters, with rates exceeding 36% in some bodybuilding populations. Significant associations were identified between AAS use and depression (Beck Depression Inventory scores significantly elevated, p<0.001), anxiety disorders (Beck Anxiety Inventory scores p<0.001), aggression and violence (meta-analytic evidence of increased interpersonal violence risk), mania and psychosis (dose-dependent), muscle dysmorphia (prevalence 58% in some AAS-using samples vs. 2-6% general population), cognitive deficits (visuospatial memory p=0.004, executive function impairment), and dependence syndromes (affecting approximately 30% of users). Neuroimaging studies demonstrated structural brain changes including cortical thinning, altered amygdala volume, and reduced frontal connectivity. Withdrawal syndrome characterized by prolonged hypogonadism and severe depression may persist for months to years. Risk factors include body image disorders (r=0.24 with obsessive-compulsive traits), competitive pressure, and polysubstance use. Conclusions: AAS use among athletes is associated with substantial psychiatric morbidity affecting mood, cognition, behavior, and brain structure. Evidence from 2015-2025 employing advanced methodologies (neuroimaging, network analysis, large-scale epidemiology) has substantially enhanced understanding. Integrated treatment approaches targeting substance use, psychiatric symptoms, and underlying body image pathology are essential. Future research priorities include longitudinal studies, gender-specific investigations, neurobiological mechanism elucidation, and evidence-based treatment trials.